1980
DOI: 10.1159/000250325
|View full text |Cite
|
Sign up to set email alerts
|

Human Epidermal Cell Proliferation with Regard to Circadian Variation of Plasma Cortisol

Abstract: This study was performed in 6 healthy young men under analogous experimental conditions to investigate whether or not the epidermal proliferative activity is influenced by the physiological circadian rhythmicity of cortisol concentration in blood. Every 6 h of total duration of the experiments, blood samples were taken for radioimmunoassay of serum cortisol and skin punch biopsies (upper arm inside) were labelled in vitro by 3H-thymidine. In 4 out of 6 individuals, an inverse and time-shifted correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Thus individually different reactions to external and internal stimuli connected with the period awake were suggested. The absence of evidence for diurnal rhythms in the S-fraction in normal human skin is in agreement with the reports of Pullmann et al (1974), Schell et al (1977) and Schell et al (1980), while Kahn, Weinstein & Frost (1968) and Thorud & Volden (1980) found minor suggestions of diurnal rhythms in ^HTdR-Iabelling indices or S-fractions in normal human skin.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Thus individually different reactions to external and internal stimuli connected with the period awake were suggested. The absence of evidence for diurnal rhythms in the S-fraction in normal human skin is in agreement with the reports of Pullmann et al (1974), Schell et al (1977) and Schell et al (1980), while Kahn, Weinstein & Frost (1968) and Thorud & Volden (1980) found minor suggestions of diurnal rhythms in ^HTdR-Iabelling indices or S-fractions in normal human skin.…”
Section: Discussionsupporting
confidence: 90%
“…In their classical animal studies on epidermal growth control, BuUough & Lawrence (i960) and Iversen, Bhangoo & Hansen (1974) experienced merely local effects of injury to epidermis. In human studies, however, it cannot be ruled out that consciousness of the procedures to be undertaken might interfere, as recently suggested by Schell et al (1980). The design of this study does not allow final statements on the existence of diurnal rhythms in the growth of human epidermis.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…1975;Akerstedt & Froberg, 1979). Schell, Hornstein & Schwarz (1980) and Schell et al (1981) reported an inverse relationship between cortisol levels and I , in human epidermis. The absence of a sleep deprivation effect on I , suggests that cortisol levels in sleep-deprived hamsters were not significantly different from those in sleeping hamsters.…”
Section: Discussionmentioning
confidence: 93%
“…Besides adrenaline-chalone com plexes [2-4] the diurnal variation of serum cortisol level influences the rate of epidermal DNA synthesis as recently demonstrated by Schell et al [12]. As another important regulatory component, the intracellular system of cyclic nucleotides (cAMP and cGMP) balances the kinetics of epidermal growth [16].…”
mentioning
confidence: 99%